PEMANFAATAN DAN PERAN KOMUNITAS LOKAL DALAM PELESTARIAN DANAU MANINJAU - Nur Hadiati Endah; M. Nadjib (Jurnal Ekonomi dan Pembangunan, 2025)
Lake Maninjau in Agam district has played a significant role for the livelihood of people in West Sumatera. This lake has been utilized for many purposes. Unfortunately, this utilization did not regard the environment. As a result, the lake becomes polluted and lose its economic value. One of the primary dilemmas in Lake Maninjau is the presence of floating net aquaculture. This activity has contributed not only to local income but also to social conflict. Thus, this article will analyze the problem of the lake management and the role of local community in Lake Maninjau. This paper is based on research report “Optimalisasi Pemanfaatan Danau Secara Multifungsi untuk Pembangunan Daerah”. Questionnaires and participative observation were applied to collect the data. Besides, researchers conducted several interviews and focus group discussion. The result showed that the local community has a positive environmental attitude, but there is a gap in their actual behavior. Finally, lack of support in term of surveillance, regulation, and cultural aspect become prominent factors to the ineffectiveness of lake management in Lake Maninjau.